Health‐oriented 'Bildung' or an obligation to a healthy lifestyle? A critical analysis of current PE curricula in Germany. Issue 1 (28th November 2020) - Ruin, Sebastian; Stibbe, Günter
Abstract : The issue of health plays an important role in the German language sports pedagogical discussion and in German curricula. It is also important here that the idea of 'Bildung'—an educational ideal in the German tradition which is still of paramount importance and which stems from the obligation of enlightenment and is intended to enable mature judgment—is a normative idea for school lessons. In terms of health in physical education, this throws up the question of whether PE for young people should not simply be focused towards a healthy lifestyle, but rather towards understanding what and how a healthy lifestyle could be and reflect on the role they want it to play in their lives in an emancipatory manner. Therefore, this paper examines the way in which health and health education are considered in current curricula in Germany. A hermeneutic oriented qualitative text analysis is carried out. Alongside differences between the states, the analysis shows an overall tendency towards narrowing down health education. The paper finally seeks to critically discuss this narrowing from a pedagogical perspective as an exemplary process which might be observed in a similar way in other countries.